PERDAGANGAN REMPAH-REMPAH DAN DAMPAKNYA TERHADAP ASIA TENGGARA - Sagita Isma Aurora; Sindy Maulana, Ellovani Boru Tarigan, Elsadai Valencia Hutagaol, Valentino Surbakti, Elly Fadilla, L (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2025)
The spice trade is a historical event that influenced various aspects of Southeast Asian society, including social, economic, cultural, and political life. This study attempts to understand the traces of the spice trade and its impact on societal change in the region from pre-colonial to the colonial era. Using historical methods with a multidisciplinary approach, this study analyzes trade routes, major types of spices, and their impacts on the economic, social, cultural, and political spheres. The results show that the spice trade not only led to economic growth but also served as a means for the spread of religion, cultural exchange, and the formation of maritime empires in Southeast Asia. The arrival of Europeans changed the way trade operated, with a system of monopolies and colonial power that brought negative impacts such as exploitation, social differences, and economic inequality that persisted into the post-colonial era.